EFFECTIVENESS OF TIKTOK SOCIAL MEDIA CONTENT ADVERTISING FOR CIBURIAL HONEYBEE FARMING AGROTOURISM USING EMPATHY AND PERSUASION DIMENSION - Syifa, Diasti Nurul; Fatimah, Sri (Universitas Galuh, 2024)
The number of social media users is increasing, including TikTok social media. TikTok is used as a marketing communication medium by businesspeople, namely Ciburial Honeybee Farming Agrotourism, who previously used Instagram but did not attract consumer interest. This research was conducted to determine how effective the video content of social media TikTok Agrotourism Ciburial Honeybee Livestock advertising is if analyzed using the empathy and persuasion dimension. The research design uses a descriptive quantitative method with survey and interview techniques. A sample size of 100 was drawn using a purposive sampling technique because the population was huge, with the criteria being active users of TikTok social media and watching advertising videos for Ciburial Honeybee Farming Agrotourism. This research uses dimensions derived from the EPIC Model, namely empathy and persuasion. This research proves that the Ciburial Honeybee Farming Agrotourism advertisement, seen from the empathy and persuasion dimension is considered effective, with an empathy score of 3.99 and persuasion 4.18. There is evaluation recommendation so that advertising effectiveness increases from practical to very effective, namely improving the quality of advertising content.